PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK DIGITAL TEMA PERKEMBANGAN TEKNOLOGI DI KELAS III SD - ame prilla amanda (PGSD UMN Al-Washliyah, 2023)
This study aims to: (1) produce Digital Scrapbook learning media on the Theme of Technology Development for Class III SD, (2) determine the feasibility of learning media for Digital Scrapbook on the Theme of Technology Development for Class III SD. From the results of the feasibility study by material experts, media experts and teacher responses. This research is a type of research and development with reference to the ADDIE model. Furthermore, the model was adapted into 3 stages, namely: (1) Analysis, (2) Design, (3) Development. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. The media expert's review sheet consists of 15 statements which are divided into 3 aspects which get an overall